Hole‐Transporting Materials in Inverted Planar Perovskite Solar Cells. Issue 17 (17th May 2016) - Yan, Weibo; Ye, Senyun; Li, Yunlong; Sun, Weihai; Rao, Haixia; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : Hybrid organic–inorganic halide‐perovskite‐based solar cells have achieved notable progress. A hot topic in this field is exploring inexpensive, stable and effective hole‐transporting materials (HTMs) in order to improve the device performance and be favorable for large‐scale production in the future. The HTMs have been proven to be an important component of perovskite solar cells, which can form selective contact being favorable for reducing charge recombination and effective hole collection, thus resulting in the enhancement of the open‐circuit voltage and the fill factor. Here, an overview of the design and development of HTMs is given, mainly divided into conductive polymers, inorganic p ‐type semiconductors in inverted‐structure‐based planar perovskite solar cells. The influences of their mobility, work function and film property on device performance are discussed. Abstract : Hole‐transporting materials in inverted planar perovskite solar cells have been widely studied in the past years. Most commonly these are p ‐type wide band‐gap semiconductors which can be mainly divided into conductive polymers and inorganic p ‐type semiconductors. Their energy levels and chemical structures are summarized and the effects of their properties on the device performance are discussed in detail.